The Saga of Olaf Tryggvason - Oddr Snorrason, active 12th century (Islandica, 2003)
"Oddr Snorrason, a Benedictine monk in northern Iceland in the late twelfth century, composed a landmark Latin biography of the legendary Norwegian king Olaf Tryggvason (died 1000 C.E.). This biography was soon translated into Icelandic, and the translation (though not the Latin original) is preserved in two somewhat differing versions and a small fragment of a third. The Saga of Olaf Tryggvason is the first English translation of this text, augmented by an introduction and notes to guide the reader."